2017
DOI: 10.1158/0008-5472.can-16-3299
|View full text |Cite
|
Sign up to set email alerts
|

SKP2 Activation by Thyroid Hormone Receptor β2 Bypasses Rb-Dependent Proliferation in Rb-Deficient Cells

Abstract: Germline RB1 mutations strongly predispose humans to cone-precursor-derived retinoblastomas and strongly predispose mice to pituitary tumors, yet shared cell type-specific circuitry that sensitizes these different cell types to the loss of RB1 has not been defined. Here we show that the cell type-restricted thyroid hormone receptor isoform TRβ2 sensitizes to RB1 loss in both settings by antagonizing the widely expressed and tumor suppressive TRβ1. TRβ2 promoted expression of the E3 ubiquitin ligase SKP2, a cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…4 and 12 and data not shown). Impaired proliferation was associated with diminished SKP2 expression and impaired S-phase entry and was partially rescued by ectopic SKP2, indicating that SKP2 is an important TR␤2 target (12).…”
Section: Tr␤2-46 But Not Tr␤2-54 Promotes Skp2-mediated Cell Cycle Prmentioning
confidence: 99%
See 4 more Smart Citations
“…4 and 12 and data not shown). Impaired proliferation was associated with diminished SKP2 expression and impaired S-phase entry and was partially rescued by ectopic SKP2, indicating that SKP2 is an important TR␤2 target (12).…”
Section: Tr␤2-46 But Not Tr␤2-54 Promotes Skp2-mediated Cell Cycle Prmentioning
confidence: 99%
“…This RNA is predicted to encode a polypeptide of 54.4 kDa (UniProt P10828, isoform ␤2). We previously found that transduction of RB177 cells with TR␤2 cDNA containing the same open reading frame mainly increased expression of TR␤2-54, based on its comigration with the major endogenous TR␤2 species (12). Thus, we sought to define the origin of the smaller TR␤2-46.…”
Section: Tr␤2-46 Translation Initiates At Methionine 79mentioning
confidence: 99%
See 3 more Smart Citations